An update on intra-abdominal hypertension and abdominal compartment syndrome in children - Veena Raghunathan; Maninder Singh Dhaliwal; Praveen Khilnani; Yatin Mehta (Journal of Pediatric Critical Care, 2016)
The concept of intra-abdominal hypertension and abdominal compartment syndrome is relatively new, but increasing awareness and evolving management strategies have been instrumental in reducing mortality by nearly half in critically ill patients with this condition. The thresholds for intraabdominal hypertension and abdominal compartment syndrome in children are different from adults. When intraabdominal pressure increases, it affects both abdominal and extra-abdominal organs. This needs to be recognised, the vicious cycle of poor perfusion and increasing intraabdominal pressure which ultimately leads to ischemic cellular necrosis. Focus has gradually shifted from treatment to prevention of progress of intraabdominal hypertension. Various non invasive methods can be used effectively to decrease intra-abdominal pressure, but surgical decompression is essential when organ dysfunction and abdominal compartment syndrome set in. This review describes the definitions, risk factors, pathophysiology and management strategies for increased intra-abdominal pressure in children.